1999
DOI: 10.1111/j.1749-6632.1999.tb07698.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐Telopeptide Pyridinoline Cross‐Links: Sensitive Indicators of Periodontal Tissue Destruction

Abstract: C-telopeptides and related pyridinoline cross-links of bone Type I collagen are sensitive markers of bone resorption in osteolytic diseases such as osteoporosis and osteoarthritis. We have studied the release of C-telopeptide pyridinoline crosslinks of Type I collagen as measures of bone destruction in periodontal disease. Studies in preclinical animal models and humans have demonstrated the relationship between radiographic bone loss and crevicular fluid C-telopeptide levels. We have recently found that C-tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Quantification of the concentrations of HP and, in particular, LP has been shown to be valuable in revealing the presence and/or extent of metastatic disease to bone in patients with oral cancers, multiple myeloma or carcinomas of the breast, lung, prostate, kidney, throat or digestive tract 31 . In accordance with other authors, it has previously been demonstrated that local alveolar bone resorption in cases of advanced periodontitis leads to elevated concentrations of HP and LP in crevicular fluid 14,21 . On this basis, it was hypothesized that infection of the mandibular bone may lead to increased urinary concentrations of HP and LP.…”
supporting
confidence: 91%
“…Quantification of the concentrations of HP and, in particular, LP has been shown to be valuable in revealing the presence and/or extent of metastatic disease to bone in patients with oral cancers, multiple myeloma or carcinomas of the breast, lung, prostate, kidney, throat or digestive tract 31 . In accordance with other authors, it has previously been demonstrated that local alveolar bone resorption in cases of advanced periodontitis leads to elevated concentrations of HP and LP in crevicular fluid 14,21 . On this basis, it was hypothesized that infection of the mandibular bone may lead to increased urinary concentrations of HP and LP.…”
supporting
confidence: 91%
“…Increased levels of ICTP have been observed in the GCF of periodontitis patients [8,14]. Lappin et al [2] reported higher median plasma concentrations of ICTP in periodontitis groups than the healthy subjects where the differences failed to reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the role of ICTP levels in gingival crevicular fluid (GCF) or peri-implant crevicular fluid as a diagnostic marker of periodontal disease activity have reported promising results so far [6,7]. ICTP has been suggested to predict future bone loss, to correlate with clinical parameters, and also to reduce following periodontal therapy [8]. Increased circulating amounts of ICTP indicate an increase in osteoclast activity.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated the role of pyridinoline cross-links to detect bone resorption in periodontitis and periimplantitis as well as in response to periodontal therapy (29,30). ICTP has been shown to be a hopeful predictor of both future alveolar bone and attachment loss.…”
Section: Markers Of Alveolar Bone Lossmentioning
confidence: 99%